SURVEI PENGGUNAAN MASKER RAMBUT BERBAHAN DASAR JAHE UNTUK PERAWATAN RAMBUT - Prastyani, Desi Nur; Kusstianti, Nia (Journal of Beauty and Cosmetology (JBC), 2021)
Chemical exposure is a factor that causes a decrease in hair health, especially when there is no adequate nutrition in the hair. This research was conducted to analyze the function of hair masks made of ginger in improving hair health. The method used is a survey. The data collection technique used was sampling on a sample of customers in one of the salons, namely Salon Tiya, totaling 100 respondents. It is in accordance with the method that the required instrument is SPSS. The results showed that 31% of respondents aged 18 years experienced damage in the form of hair loss. Meanwhile, 55% have never used a ginger mask. Most of the respondents do not understand the ingredients in the hair care products they use, especially anti-dandruff products. Keywords: ginger mask, hair care, survey